ANALYSIS OF AFFECTING FACTORS POVERTY RATE IN THE PROVINCE SUMATERA ISLAND - Almaya Elvira; Murtala; Aiyub Yahya (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
This study examined the factors influencing poverty levels in the provinces of Sumatra Island with the average length of schooling, open unemployment rate, economic growth, and population density as the independent variables. This study used secondary data from 2007 to 2020. The regression model used was a panel data regression model with three kinds of estimates, namely the common effect model, the fixed-effect model, and the random effect model. To select the appropriate model, it was tested through three tests, including the Chow test, Hausmant test, and LM test. Based on the test results, the model selected in this study was the fixed effect model. The regression tool was Eviews 9. The results showed that the average length of schooling and the open unemployment rate affect the poverty level in the provinces of Sumatra island. Meanwhile, economic growth and population density did not affect the poverty levels in the provinces of Sumatra Island.